Global strategic management in the service industry : a perspective of the new era - Tabari, Saloomeh; Chen, Wei, 1971- (Emerald Publishing Limited, 2022)
Global Strategic Management in the Service Industry: A Perspective of the New Era covers recent changes within the service industry during the COVID-19 Pandemic and new and emerging consumer trends, providing a holistic view of this new era within the service industry. Across a range of thematic chapters, issues in digital marketing, online retailing and experiential marketing are examined, as well as the challenges faced by small and large businesses in the service sector. Tabari and Chen provide a fresh view of changes in the strategic management and marketing strategies within the service industry, exchanging new ideas for both the mid and post-pandemic crisis. Global Strategic Management in the Service Industry illustrates how strategic managers in service industry appraise the sectors in which their organisations are involved; appraise their competitors; and reassess their strategy and fix goals to meet all the challenges presented. This is important particularly due to rapid growth and technological advancements developed in service sectors being applied to other industries.
Keywords: Service industries -- Management.; Strategic planning.; COVID-19 Pandemic, 2020- -- Economic aspects.; Business & Economics -- Management.; Management & management techniques.; elektronické knihy; electronic books